A20 as a novel prognostic factor for recurrence and patients' survival in oral squamous cell carcinoma - Spörl, Silvia; Erber, Ramona; Gerken, M.; Fischer, R.; Taxis, J.; Meier, J. K.; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckhove, P.; Mackensen, Andreas; Reichert, T.; Spanier, G.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

A20 as a Potential New Tool in Predicting Recurrence and Patient’s Survival in Oral Squamous Cell Carcinoma - Spoerl, Steffen; Erber, Ramona; Gerken, Michael; Taxis, Juergen; Ludwig, Nils; Nieberle, Felix; Biermann, Niklas; Geppert, Carol-Immanuel; Ettl, Tobias; Hartmann, Arndt; Beckhove, Philipp; Reichert, Torsten E.; et al. (Cancers, 2023)
A20, known as a potent inhibitor of NF-κB signaling, has been characterized in numerous clinical as well as preclinical studies. Recently, especially in various malignant diseases, the prognostic and therapeutic relevance of A20 was investigated. In oral squamous cell carcinoma (OSCC) however, the characterization of A20 is uncharted territory. We analyzed a tissue microarray (TMA) of 229 surgically-treated OSCC patients (2003–2013). Immunohistochemical (IHC) stainings were performed for A20 and CD3; additionally, standard haematoxylin-eosin staining was applied. IHC findings were correlated with a comprehensive dataset, comprising clinical and pathohistological information. A20 expression was analyzed in tumor cells as well as in tumor infiltrating lymphocytes (TILs) and correlated with the overall survival (OS) and recurrence-free survival (RFS) using uni- and multivariable Cox regression. The median follow-up time was 10.9 years and the A20 expression was significantly decreased in CD3+ TILs compared to mucosa-infiltrating lymphocytes (MILs). In the Kaplan–Meier analyses, higher A20 expression in TILs was correlated with better OS (p = 0.017) and RFS (p = 0.020). In the multivariable survival analysis, A20 overexpression correlated with improved OS (HR: 0.582; 95% CI 0.388–0.873, p = 0.009) and RFS (HR 0.605; 95% CI 0.411–0.889, p = 0.011). Our results indicate a novel prognostic role for A20 in OSCC. Due to its elevated expression in TILs, further research is highly desirable, which therefore could offer new therapeutic opportunities for patients suffering from OSCC.
CRIS-Team Scopus Importer:2023-02-24
Keywords: A20; oral squamous cell carcinoma; OSCC; tissue microarray; TNFAIP3

Anti-angiogenic therapy in head and neck squamous cell carcinoma - current limitations and future directions - Nieberle, Felix; Spoerl, Steffen; Głuszko, Alicja; Taxis, Juergen; Spanier, Gerrit; Erber, Ramona; Spörl, Silvia; Szczepański, Mirosław J.; Beckhove, Philipp; Reichert, Torsten E.; Whiteside, Theresa L.; Ludwig, Nils (Vessel Plus, 2024)
Angiogenesis, the formation of new blood vessels, plays a crucial role in the progression and metastasis of various cancers, including head and neck squamous cell carcinoma (HNSCC). HNSCCs are characterized by altered levels of angiogenesis-related factors, including the overexpression of pro-angiogenic factors such as vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF), as well as the dysregulation of angiogenesis inhibitors. Together, these factors drive the formation of new blood vessels within the tumor microenvironment and are considered therapeutic targets in HNSCC. Although preclinical studies are promising, challenges have emerged in the clinical use of anti-angiogenic agents in the clinic, including treatment-related toxicities and the development of resistance to therapy. There is an unmet need for further research to elucidate the molecular pathways involved in HNSCC angiogenesis, identify novel therapeutic targets, and discover predictive biomarkers to improve patient selection.
CRIS-Team Scopus Importer:2024-07-19
Keywords: antiangiogenic therapy; Head and neck squamous cell carcinoma; HNSCC; oral squamous cell carcinoma; OSCC; tumor angiogenesis

CAR T-cell therapy rescues adolescent with rapidly progressive lupus nephritis from haemodialysis - Krickau, Tobias; Naumann-Bartsch, Nora; Aigner, Michael; Kharboutli, Soraya; Kretschmann, Sascha; Spörl, Silvia; Vasova, Ingrid; Völkl, Simon; Wölfle, Joachim; Mackensen, Andreas; Schett, Georg; Metzler, Markus; et al. (Lancet, 2024)
CRIS-Team Scopus Importer:2024-05-03

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

CD19-targeting CAR T-cell therapy in patients with diffuse systemic sclerosis: a case series - Auth, Janina; Müller, Fabian; Völkl, Simon; Bayerl, Nadine; Distler, Jörg H.W.; Tur, Carlo; Raimondo, Maria Gabriella; Chenguiti Fakhouri, Sara; Atzinger, Armin; Coppers, Birte; Eckstein, Markus; Liphardt, Anna-Maria; et al. (The Lancet Rheumatology, 2024)
Background: CD19-targeting chimeric antigen receptor (CAR) T-cell therapy has shown remarkable outcomes in patients with systemic lupus erythematosus. The effects of CD19-targeting CAR T cells on organ manifestations in patients with systemic sclerosis have yet to be characterised. B cells have a central role in the pathogenesis of systemic sclerosis. We present a detailed analysis of the effects of CD19-targeting CAR T-cell therapy in patients with systemic sclerosis. Methods: Six patients with severe diffuse systemic sclerosis with an insufficient response to at least two treatments were consecutively recruited at the Department of Internal Medicine 3, University Hospital Erlangen (Erlangen, Germany) to receive CD19-targeting CAR T-cell treatment (1 × 106 CAR T cells per kg bodyweight). Events were predefined by progression of interstitial lung disease, onset of congestive heart failure, onset of renal failure, onset of arterial hypertension, or initiation of new immunosuppressive or antifibrotic therapy. Event-free time or treatment intensification after study entry was the primary outcome. Key secondary outcomes included changes in the modified Rodnan Skin Score (mRSS), imaging (a component of the assessment of lung fibrosis), laboratory assessments, patient-reported outcomes, and a modified version of the American College of Rheumatology Composite Response Index in Systemic Sclerosis (ACR-CRISS), assessed at baseline, 3 months, 6 months, 9 months, and 12 months. Findings: Between April 20, 2022, and Nov 8, 2023, six patients with severe diffuse systemic sclerosis (median age 42 years [IQR 36–53]; four men and two women; all White European) were recruited and received CD19-targeted CAR T-cell therapy. The median follow-up time was 487 days (IQR 342–585). No events occurred within the observational period. Probability of improvement in the ACR-CRISS score increased to a median of 100% (IQR 100–100) at 6 months. Median mRSS decreased by 31% (IQR 29–38), corresponding to a median of 8 points (IQR 7–13) within 100 days. The extent of disease on CT scan decreased by a median of 4% (IQR 3–4) due to reduction of ground-glass opacities while the reticular pattern remained stable. Forced vital capacity improved by a median of 195 mL (IQR 18–275) at the latest observational timepoint. Interpretation: We provide the first evidence that CD19-targeting CAR T-cell therapy might intercept with the progression of fibrotic organ manifestations in patients with systemic sclerosis. Funding: Deutsche Forschungsgemeinschaft, Deutsche Krebshilfe, ELAN-Foundation Erlangen, IZKF Erlangen, and Bundesministerium für Bildung und Forschung.
CRIS-Team Scopus Importer:2024-12-13

Clinical significance of panendoscopy in initial staging of oral squamous cell carcinoma and detection of synchronous second malignancies of the upper aerodigestive tract — Insights from a retrospective population-based cohort study - Spoerl, Steffen; Gerken, Michael; Chamilos, Christos; Spörl, Silvia; Fischer, René; Vielsmeier, Veronika; Künzel, Julian; Bohr, Christopher; Meier, Johannes K.; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Journal of Cranio-Maxillofacial Surgery, 2022)
The aim of this study was to examine the prevalence of synchronous upper aerodigestive tract (UAT) tumors within oral squamous cell carcinoma (OSCC) patients, and to specify distinct risk groups who benefit from panendoscopy. Definite clinical and pathohistological characteristics, as well as overall and recurrence-free survival (OAS and RFS, respectively) of OSCC patients with and without synchronous second UAT tumors, carcinomas in situ, or higher-grade dysplasia/metaplasia, were evaluated based on a retrospective population-based cohort study, including alignment with cancer registry data. Out of 727 included OSCC patients, 465 cases (64.0%) received panendoscopy. Among these, 18 UAT tumors were detected, all of which were linked to patients with a positive history of nicotine abuse. Every synchronous UAT tumor was revealed by panendoscopy, which, analyzed as an independent staging procedure, was accompanied by a low complication rate (1.7%). When illuminating the impact of a second UAT tumor in OSCC patients, survival analysis revealed reduced 5-year OAS (63.9% vs 43.5%, p = 0.010) and RFS (57.1% vs 32.4%, p = 0.016) for patients with a second oncology diagnosis of the UAT. Within the limitations of the study, it seems that panendoscopy should be performed in the majority of patients suffering from OSCC, because most of them have a history of smoking and drinking, which correlates with an increased risk of developing synchronous UAT tumors.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Oral cancer; Oral squamous cell carcinoma; Panendoscopy; Risk factor; Staging; Synchronous second carcinoma; Upper aerodigestive tract

CXCR2 expression on neutrophil granulocytes in peripheral tumor is associated with shorter survival in oral squamous cell carcinoma - Spörl, Silvia; Erber, Ramona; Gerken, M.; Wittenberg, M.; Fischer, R.; Taxis, J.; Hartmann, Arndt; Geppert, Carol-Immanuel; Mamilos, A.; Mackensen, Andreas; Reichert, T.; Spanier, G.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Early clinical trial unit tumor board: a real-world experience in a national cancer network - Weiss, L.; Dorman, K.; Boukovala, M.; Schwinghammer, F.; Jordan, P.; Fey, T.; Hasselmann, K.; Subklewe, M.; Bücklein, V.; Bargou, R.; Goebeler, M.; Sayehli, C.; et al. (Journal of Cancer Research and Clinical Oncology, 2023)
Purpose: Early clinical trials are the first step into clinical therapies for new drugs. Within the six Bavarian university-based hospitals (Augsburg, Erlangen, Regensburg, Munich (LMU and TU), Würzburg) we have enrolled a virtual network platform for patient discussion. Methods: The virtual Early Clinical Trial Unit Tumor Board (ECTU Tumor Board) is a secured web-based meeting to evaluate early clinical trial options for patients, where representatives from local ECTUs participate. We retrospectively analyzed patient cases discussed between November 2021 and November 2022. Results: From November 2021 to November 2022, a total of 43 patients were discussed in the ECTU Tumor Board. Median age at diagnosis was 44.6 years (range 10–76 years). The median number of previous lines of therapies was 3.7 (range 1–9 therapies) including systemic treatment, surgery, and radiation therapy. A total of 27 different tumor entities were presented and 83.7% (36/43) patients received at least one trial recommendation. In total, 21 different active or shortly recruiting clinical trials were recommended: ten antibody trials, four BiTE (bispecific T cell engager) trials, six CAR (chimeric antigen receptor) T-cell trials, and one chemotherapy trial. Only six trials (28.6%) were recommended on the basis of the previously performed comprehensive genetic profiling (CGP). Conclusion: The ECTU Tumor Board is a feasible and successful network, highlighting the force of virtual patient discussions for improving patient care as well as trial recruitment in advanced diseases. It can provide further treatment options after local MTB presentation, aiming to close the gap to access clinical trials.
CRIS-Team Scopus Importer:2023-08-04
Keywords: Clinical trials; Early clinical trial; ECTU; Interdisciplinary; Precision oncology; Tumor board

Enasidenib in IDH-2 mutant AML patients with relapse after allogeneic stem cell transplantation - Vasova, Ingrid; Spörl, Silvia; Guggenberger, Valentin; Berisha, M.; Rech, D.; Behzad, Ali; Brandt, Amelie; Kremer, A.; Mackensen, Andreas; Rösler, Wolf; Winkler, J. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Expression of vesiculation-related genes is associated with a tumor-promoting microenvironment: a pan-cancer analysis - Westermann, Luisa; Diergaarde, Brenda; Heidegger, Simon; Poeck, Hendrik; Szczepański, Mirosław J.; Reichert, Torsten E.; Spörl, Silvia; Whiteside, Theresa L.; Spoerl, Steffen; Ludwig, Nils (Clinical & Translational Oncology, 2025)
Background: Small extracellular vesicles (sEV) released by tumor cells (tumor-derived sEV; TEX) mediate intercellular communication between tumor and non-malignant cells and were shown to impact disease progression. This study investigates the relationship between the expression levels of the vesiculation-related genes linked to sEV production and the tumor microenvironment (TME). Methods: Two independent gene sets were analyzed, both previously linked to sEV production in various non-malignant or malignant cells. Expression profiles were compared among 28 tumor types listed in the Cancer Genome Atlas (TCGA). Gene expression and survival analysis (GEPIA2), immunogenomic analysis (TISIDB), and genomic analysis (GSCA) were performed. Results: Vesiculation-related genes were overexpressed in tissues of most tumor types compared to healthy tissues, and high expression levels were associated with worse overall survival in cervical squamous cell carcinoma, kidney chromophobe, lower grade glioma, hepatocellular carcinoma, lung squamous cell carcinoma, and pancreatic adenocarcinoma but with improved overall survival in kidney renal clear cell carcinoma. Expression of these signatures correlated with an increased abundance of infiltrating CD4( +) T cells and dendritic cells, a decreased abundance of B cells and eosinophils, and activation of tumor cell apoptosis and epithelial–mesenchymal transition pathways in all tumor types. 17-AAG was identified as a potential drug candidate to target tumors with elevated expression of vesiculation-related genes. Conclusions: Vesiculation-related genes were associated with distinct immunological and genomic landscapes further emphasizing the important role of TEX in cancer progression.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Exosomes; Extracellular vesicles; Tumor microenvironment; Tumor-infiltrating immune cells; Vesiculation-related genes

Head and neck melanoma: outcome and predictors in a population-based cohort study - Spoerl, Steffen; Spanier, Gerrit; Reiter, Elena; Gerken, Michael; Haferkamp, Sebastian; Grosse, Jirka; Drexler, Konstantin; Ettl, Tobias; Klinkhammer-Schalke, Monika; Fischer, Rene; Spörl, Silvia; Reichert, Torsten E.; et al. (Head & Face Medicine, 2021)
Background To evaluate predictive clinico-pathological characteristics on outcome in head and neck melanoma (HNM) in a population-based study with particular emphasis on the prognostic effect of sentinel lymph node biopsy (SLNB), Charlson comorbidity index (CCI) and distinct tumor localisations. Methods Here we primarily describe a retrospective multicenter population-based cohort study with 402 patients having undergone resection with curative intent of HNM between 2010 and 2017. SLNB was used in the diagnosis of 79 HNM patients. Outcome was analyzed, focusing on SLNB, CCI as well as tumor localisation. Overall survival (OAS) und recurrence free survival (RFS) was examined by uni- and multivariate analysis. Results Histopathologically verified lymph node metastasis according to SLNB was associated with impaired RFS in HNM patients (p = 0.004). Especially in higher tumor stages, the sole implementation of SLNB improved survival significantly in the present cohort (p = 0.042). With most of the HNM being located in the face, melanoma of the scalp and neck could be linked to deteriorated patient's outcome in uni- as well as multivariate analysis (p = 0.021, p = 0.004). Conclusions SLNB is a useful tool in predicting development of distant metastasis after HNM resection with curative intent. Especially in higher tumor stages, performing a SLNB ameliorated survival of HNM patients. Additionally, CCI as well as a distinct tumor localisations in HNM were identified as important risk factors in our population-based cohort study.
CRIS-Team WoS Importer:2021-11-05

Identification of Disparities in Personalized Cancer Care—A Joint Approach of the German WERA Consortium - Lüke, Florian; Haller, Florian; Utpatel, Kirsten; Krebs, Markus; Meidenbauer, Norbert; Scheiter, Alexander; Spörl, Silvia; Heudobler, Daniel; Sparrer, Daniela; Kaiser, Ulrich; Keil, Felix; Schubart, Christoph; et al. (Cancers, 2022)
(1) Background: molecular tumor boards (MTBs) are crucial instruments for discussing and allocating targeted therapies to suitable cancer patients based on genetic findings. Currently, limited evidence is available regarding the regional impact and the outreach component of MTBs; (2) Methods: we analyzed MTB patient data from four neighboring Bavarian tertiary care oncology centers in Würzburg, Erlangen, Regensburg, and Augsburg, together constituting the WERA Alliance. Absolute patient numbers and regional distribution across the WERA-wide catchment area were weighted with local population densities; (3) Results: the highest MTB patient numbers were found close to the four cancer centers. However, peaks in absolute patient numbers were also detected in more distant and rural areas. Moreover, weighting absolute numbers with local population density allowed for identifying so-called white spots—regions within our catchment that were relatively underrepresented in WERA MTBs; (4) Conclusions: investigating patient data from four neighboring cancer centers, we comprehensively assessed the regional impact of our MTBs. The results confirmed the success of existing collaborative structures with our regional partners. Additionally, our results help identifying potential white spots in providing precision oncology and help establishing a joint WERA-wide outreach strategy.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cancer care; MTB; outcomes research; outreach; patient access; precision oncology; real world data

Impact of spatially heterogeneous trop‐2 expression on prognosis in oral squamous cell carcinoma - Erber, Ramona; Spoerl, Steffen; Mamilos, Andreas; Krupar, Rosemarie; Hartmann, Arndt; Rübner, Matthias; Taxis, Juergen; Wittenberg, Mareike; Reichert, Torsten E.; Spanier, Gerrit; Spörl, Silvia (International Journal of Molecular Sciences, 2022)
Oral cancer often presents with aggressive behavior and a high risk of recurrence and metastasis. For oral squamous cell carcinoma (OSCC), which is the most frequent histological subtype, therapy strategies include surgery, radiation therapy, chemotherapy, immune checkpoint inhibitors, and EGFR inhibitors. Recently, a Trop‐2 antibody‐drug conjugate (ADC) has been approved in the United States of America for the treatment of advanced triple‐negative breast cancer. However, this ADC has also been tested in other solid tumors including head & neck squamous cell carcinoma. The prognostic impact of Trop‐2 has already been reported for several cancers. We studied the prognostic influence of Trop‐2 protein expression on OSCC patients’ survival. The cohort comprised n = 229 OSCC patients with available archived tumor tissue and corresponding non‐neoplastic oral mucosa tissue. Using immunohistochemistry, we investigated Trop‐2 expression in both the central and peripheral regions of each tumor and in corresponding non‐neoplastic oral mucosa. In patients suffering from OSCC with combined high central and low peripheral Trop‐2 expression, five‐year overall survival (OS) was 41.2%, whereas 55.6% of OSCC patients who presented lower central and/or higher peripheral tumoral Trop‐2 expression were alive after five years (p = 0.075). In multivariate Cox regression, the expression pattern of high central tumoral and lower peripheral Trop‐2 expression was significantly correlated with impaired OS (HR = 1.802, 95%‐CI: 1.134–2.864; p = 0.013) and recurrence‐free survival (RFS) (HR = 1.633, 95%‐CI: 1.042–2.560; p = 0.033), respectively, when adjusting for co‐variables. Hence, Trop‐2 may serve as an independent prognostic biomarker in OSCC. In subsequent studies, the pathophysiological meaning of downregulated Trop‐2 expression in the OSCC periphery has to be analyzed.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antibody‐drug conjugates; Biomarker; Head and neck cancer; Immunohistochemistry; Oral squamous cell carcinoma; Prognosis; TACSTD2; Trop‐2; Tumor associated calcium signal transducer 2

Oligoclonal CD4+CXCR5+ T cells with a cytotoxic phenotype appear in tonsils and blood - Liang, Chunguang; Spörl, Silvia; Xiao, Yin; Habenicht, Katharina M.; Haeusl, Sigrun S.; Sandner, Isabel; Winkler, Julia; Strieder, Nicholas; Eder, Rüdiger; Stanewsky, Hanna; Alexiou, Christoph; Dudziak, Diana; et al. (Communications Biology, 2024)
Most subsets of CD4+ T-follicular helper cells occur in blood and tonsils, but location enforces specific gene expression. One subtype reveals a cytotoxic phenotype, is circulating or extrafollicular, oligoclonal and shares TCRs with other clusters.
CRIS-Team Scopus Importer:2024-07-26

Prognostic Relevance of Type 2 Diabetes and Metformin Treatment in Head and Neck Melanoma: Results from a Population-Based Cohort Study - Spoerl, Steffen; Gerken, Michael; Schimnitz, Susanne; Taxis, Juergen; Fischer, Rene; Lindner, Sophia R. R.; Ettl, Tobias; Ludwig, Nils; Spörl, Silvia; Reichert, Torsten E. E.; Spanier, Gerrit (Current Oncology, 2022)
Background: Type 2 Diabetes (DM2) and the consecutively daily use of antidiabetic medication are characterized by a frequent prevalence worldwide and were shown to impact the initiation and progression of malignant diseases. While these effects were observed in a variety of malignancies, comprehensive data about the role of DM2 and antidiabetic drugs in the outcome of head and neck melanoma (HNM) patients are missing. Methods: This retrospective population-based cohort study included 382 HNM patients from Eastern Bavaria having received tumor resection to negative margins between 2010 and 2017. Recurrence-free survival (RFS) was evaluated with regard to DM2 and routine metformin intake. Statistical analysis was performed by uni- and multivariate analyses. The median follow-up time was 5.6 years. Results: DM2 was diagnosed in 68 patients (17.8%), routine metformin intake was found in 39 cases (10.2%). The univariate survival analysis revealed impaired 5-year RFS in HNM patients with DM2 compared to non-diabetic controls (p = 0.016; 64.0% and 74.5%, respectively). The multivariate Cox regression substantiated this effect (HR = 1.980, 95% CI = 1.108-3.538, p = 0.021). In detail, the cumulative locoregional recurrence rate displayed the most far-reaching negative effect on the RFS of diabetic HNM patients (HR = 4.173, 95% CI = 1.628-10.697, p = 0.003). For metformin intake, a profound positive effect on the RFS in multivariate statistics was observed, both in the complete cohort (HR = 0.396, 95% CI = 0.177-0.884, p = 0.024) as well as in the cohort of diabetic HNM patients (HR = 0.352, 95% CI = 0.135-0.913, p = 0.032). Conclusions: This study emphasizes that DM2 is a relevant comorbid condition in HNM patients, impairing patient survival. Metformin intake was associated with a favorable outcome in HNM patients, providing possible therapeutic implications for future adjuvant treatment regimes.
CRIS-Team WoS Importer:2023-01-06

Prognostic Value of Perineural Invasion on Survival and Recurrence in Oral Squamous Cell Carcinoma - Spoerl, Steffen; Spörl, Silvia; Reil, Stephanie; Gerken, Michael; Ludwig, Nils; Taxis, Juergen; Fischer, René; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Diagnostics, 2022)
A diagnosis of perineural invasion (PNI) is widely accepted as an unfavorable prognostic factor in various solid malignancies. Although PNI has been described as a high-risk parameter in oral squamous cell carcinoma (OSCC), its role in the current staging manuals of the American Joint Committee on Cancer (AJCC) is rather subordinate. We analysed the prognostic value of PNI on survival and recurrence in a large, multicenter OSCC cohort and a population-based approach. A total of 493 OSCC patients with primary tumor resection to negative margins and concomitant neck dissection between 2010 and 2017 were enrolled. PNI was evaluated in relation to overall survival (OAS) and recurrence-free survival (RFS) using uni-and multi-variable Cox regression. The median follow-up time was 5.0 years and PNI was diagnosed in 48 patients (9.7%). A patho-histological verification of PNI correlated significantly with a deteriorated OAS in uni-(HR 2.312; 95% CI 2.312–3.493, p = 0.001) and multivariable Cox regression (HR 1.820; 95% CI 1.164–2.847, p = 0.009). Additionally, a diagnosis of PNI correlated with increased cumulative, as well as distant, metastasis 5-year-recurrence rates (p = 0.027 and p = 0.011, respectively). The application of adjuvant radiotherapy (RT) or radiochemotherapy (RCT) in patients with PNI did not alter OAS or RFS in survival analysis when compared to patients without PNI. The results underline the adverse impact of PNI on the survival and recurrence of surgically treated OSCC patients. Based on our findings, we highly recommend an emphasis on PNI in the TNM staging concept.
CRIS-Team Scopus Importer:2022-05-20
Keywords: oral cancer; oral squamous cell carcinoma; perineural invasion; PNI; recurrence; survival

Recording of the regional Origin Areas of Patients from the Molecular Tumor Board to Identify the "white Spots" in the Service Area - A joint Initiative of the Bavarian CCC WERA Alliance - Lueke, F.; Haller, F.; Utpatel, K.; Krebs, M.; Meidenbauer, Norbert; Scheiter, A.; Spörl, Silvia; Heudobler, D.; Keil, F.; Schubart, Christoph; Tögel, Lars; Einhell, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Severity of COVID-19 disease is related to hyperactivation and altered migratory capacity of T cells - Spörl, Silvia; Kremer, Anna-Lena; Aigner, Michael; Eisenhauer, Nina; Koch, P.; Meretuk, L.; Loeffler, P.; Lutzny-Geier, Gloria; Vetter, Marcel; Bruns, Heiko; Mackensen, Andreas; Kremer, Andreas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Statin Use Ameliorates Survival in Oral Squamous Cell Carcinoma-Data from a Population-Based Cohort Study Applying Propensity Score Matching - Spoerl, Steffen; Gerken, Michael; Fischer, Rene; Spörl, Silvia; Kirschneck, Christian; Wolf, Stefanie; Taxis, Juergen; Ludwig, Nils; Biermann, Niklas; Reichert, Torsten E.; Spanier, Gerrit (Biomedicines, 2023)
The anti-cancer properties of statins have attracted much attention recently, but little is known about the prognostic role of statins in oral squamous cell carcinoma (OSCC). In a retrospective approach, we analyzed a population-based cohort of 602 OSCC patients with primary curative tumor resection to negative margins and concomitant neck dissection between 2005-2017. Long-term medication with statins was correlated with overall survival (OAS) as well as recurrence-free survival (RFS) using uni- and multivariable Cox regression. Additionally, propensity score matching was applied to adjust for confounders. Statin use was present in 96 patients (15.9%) at a median age of 65.7 years. Statin treatment correlated with ameliorated survival in multivariable Cox regression in the complete cohort (OAS: HR 0.664; 95% CI 0.467-0.945, p = 0.023; RFS: HR 0.662; 95% CI 0.476-0.920, p = 0.014) as well as matched-pair cohort of OSCC patients (OAS: HR 0.691; 95% CI 0.479-0.997, p = 0.048; RFS: HR 0.694; 95% CI 0.493-0.976, p = 0.036) when compared to patients not taking statins at time of diagnosis. These findings were even more pronounced by sub-group analysis in the matched-pair cohort (age < 70 years). These data indicate that statin use might ameliorate the oncological outcome in primarily resected OSCC patients, but prospective clinical trials are highly recommended.
CRIS-Team WoS Importer:2023-03-17

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

The WERA cancer center matrix: Strategic management of patient access to precision oncology in a large and mostly rural area of Germany - Krebs, Markus; Haller, Florian; Spörl, Silvia; Gerhard-Hartmann, Elena; Utpatel, Kirsten; Maurus, Katja; Kunzmann, Volker; Chatterjee, Manik; Venkataramani, Vivek; Maatouk, Imad; Bittrich, Max; Einwag, Tatjana; et al. (European Journal of Cancer, 2024)
Purpose: Providing patient access to precision oncology (PO) is a major challenge of clinical oncologists. Here, we provide an easily transferable model from strategic management science to assess the outreach of a cancer center. Methods: As members of the German WERA alliance, the cancer centers in Würzburg, Erlangen, Regensburg and Augsburg merged care data regarding their geographical impact. Specifically, we examined the provenance of patients from WERA´s molecular tumor boards (MTBs) between 2020 and 2022 (n = 2243). As second dimension, we added the provenance of patients receiving general cancer care by WERA. Clustering our catchment area along these two dimensions set up a four-quadrant matrix consisting of postal code areas with referrals towards WERA. These areas were re-identified on a map of the Federal State of Bavaria. Results: The WERA matrix overlooked an active screening area of 821 postal code areas – representing about 50 % of Bavaria´s spatial expansion and more than six million inhabitants. The WERA matrix identified regions successfully connected to our outreach structures in terms of subsidiarity – with general cancer care mainly performed locally but PO performed in collaboration with WERA. We also detected postal code areas with a potential PO backlog – characterized by high levels of cancer care performed by WERA and low levels or no MTB representation. Conclusions: The WERA matrix provided a transparent portfolio of postal code areas, which helped assessing the geographical impact of our PO program. We believe that its intuitive principle can easily be transferred to other cancer centers.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Cancer care facilities; Community health services; Health services administration; Healthcare disparities; Intersectoral collaboration; Tertiary healthcare

TIGIT Expression on Intratumoral Lymphocytes Correlates with Improved Prognosis in Oral Squamous Cell Carcinoma. - Eichberger, Jonas; Spörl, Silvia; Spanier, Gerrit; Erber, Ramona; Taxis, Juergen; Schuderer, Johannes; Ludwig, Nils; Fiedler, Mathias; Nieberle, Felix; Ettl, Tobias; Geppert, Carol-Immanuel; Reichert, Torsten E.; et al. (Biomedicines, 2022)
(1) Background: T-cell immunoglobulin and ITIM domain (TIGIT) is a potential immunotherapeutic target in a variety of malignant entities, and antibody-based treatments are currently under investigation in clinical trials. While promising results were observed in patients with lung cancer, the role of TIGIT in oral squamous cell carcinoma (OSCC) as a biomarker as well as a therapeutic target remains elusive. Therefore, we evaluated the role of TIGIT as a prognostic factor in OSCC. (2) Methods: Here, we describe the results of a retrospective tissue microarray (TMA) OSCC cohort. Using immunohistochemistry, TIGIT expression was correlated with overall and recurrence-free survival (OAS and RFS, respectively). Additionally, in silico analysis was performed based on the TCGA Head and Neck Squamous Cell Carcinoma (HNSCC) cohort in order to correlate patients' survival with TIGIT and CD274 (encoding for PD-L1) gene expression levels. (3) Results: Database analysis revealed a beneficial outcome in OAS for tumor patients with high intraepithelial CD3-TIGIT-expression (n = 327). Hereby, OAS was 53.9 months vs. 30.1 months for patients with lower TIGIT gene expression levels (p = 0.033). In our retrospective OSCC-TMA cohort, elevated TIGIT levels on CD3+ cells correlated significantly with improved OAS (p = 0.025) as well as distant RFS (p = 0.026). (4) Conclusions: This study introduces TIGIT as a novel prognostic factor in OSCC, indicating the improved outcome of OSCC patients relative to their increased TIGIT expression. TIGIT might provide therapeutic implications for future immunotherapy in advanced-stage OSCC patients.
EVALuna2:513924

Treatment of CNS systemic lupus erythematosus with CD19 CAR T cells - Hagen, Melanie; Müller, Fabian; Wirsching, Andreas; Kharboutli, Soraya; Spörl, Silvia; Aigner, Michael; Völkl, Simon; Köhler, Birgit; Dörfler, Arnd; Grieshaber Bouyer, Ricardo; Mackensen, Andreas; Schett, Georg (The Lancet, 2024)
CRIS-Team Scopus Importer:2024-12-02